2010
DOI: 10.1111/j.1601-5215.2010.00459.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal grey matter in victims of rape with PTSD in Mainland China: a voxel-based morphometry study

Abstract: The findings of abnormal GMD in VoR with PTSD support the hypothesis that PTSD is associated with widespread anatomical changes in the brain. The medial frontal cortex, precentral cortex, posterior cingulate cortex, post-central cortex and inferior parietal lobule may play important roles in the neuropathology of PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 72 publications
(92 reference statements)
1
22
0
Order By: Relevance
“…Due to their post-hoc nature, we do not interpret these findings, but merely report them for completeness. These findings are consistent with the anatomical location, but not necessarily the direction, of previously reported associations between PTSD trauma load andgray matter volume of the postcentral gyrus, middle frontal gyrus, fusiform, gyrus and frontal inferior gyrus (Felmingham et al, 2009; Kroes, Rugg, Whalley, & Brewin, 2011a; Nardo et al, 2010; Sui et al, 2010; Tavanti et al, 2012). We also found structural volume withinthe cerebellum to be positively associated with greater endorsement of PTSD symptomatology.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Due to their post-hoc nature, we do not interpret these findings, but merely report them for completeness. These findings are consistent with the anatomical location, but not necessarily the direction, of previously reported associations between PTSD trauma load andgray matter volume of the postcentral gyrus, middle frontal gyrus, fusiform, gyrus and frontal inferior gyrus (Felmingham et al, 2009; Kroes, Rugg, Whalley, & Brewin, 2011a; Nardo et al, 2010; Sui et al, 2010; Tavanti et al, 2012). We also found structural volume withinthe cerebellum to be positively associated with greater endorsement of PTSD symptomatology.…”
Section: Discussionsupporting
confidence: 91%
“…Early studies showed reduced volume within the pregenual and subcallosal cortex, which also includes regions of the medial prefrontal and orbitofrontal cortex (Chen, Li, Xu, & Liu, 2009; Felmingham et al, 2009; Geuze et al, 2008; Sui et al, 2010; Tavanti et al, 2012; Thomaes et al, 2010), among women with PTSD compared to trauma-exposed women without PTSD (Rauch et al, 2003). This finding has been replicated across a number of studies (Chen et al, 2006; Eckart et al, 2011; Felmingham et al, 2009; Ferrari, Busatto, McGuire, & Crippa, 2008; Thomaes et al, 2010; Yamasue et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The precentral gyrus is thought to be part of the so-called fear-related motor neurocircuitry (37,38) and has been shown to have a larger grey matter volume in rape victims with PTSD than without PTSD. In light of our present findings, this may potentially be mediated by levels of peritraumatic and post-traumatic dissociation (39). The fusiform gyrus is known to subserve visual imagery from a first-person perspective (40) and is involved in cognitive forms of emotion regulation (36).…”
Section: Discussionmentioning
confidence: 95%
“…By contrast, some studies exhibited that the deactivation of fusiform gyrus in PTSD involved in complex visual emotional processing (Bremner et al ., ), retrieval of emotionally valenced word pairs (Bremner, ) and movie‐induced positive emotional processing (Jatzko et al ., ). Additionally, structural MRI study of PTSD indicated that grey matter density of fusiform gyrus was significantly reduced in patients compared to healthy controls (Sui et al ., ). Failure to replicate the consistent fusiform gyrus responsivity may be due to different task paradigms or type II error associated with small sizes.…”
Section: Discussionmentioning
confidence: 97%